MS-275 induces hepatic FGF21 expression via H3K18ac-mediated CREBH signal. (May 2019) - Zhang, Qi; Zhu, Qin; Deng, Ruyuan; Zhou, Feiye; Zhang, Linlin; Wang, Shushu; Zhu, Kecheng; Wang, Xiao; Zhou, Libin; Su, Qing
Abstract : Fibroblast growth factor 21 (FGF21) plays an important role in the regulation of lipid and glucose metabolism. MS-275, as a class I-specific histone deacetylase (HDAC) inhibitor, has also been reported to affect energy metabolism. In this current study, we investigated the effects of MS-275 on hepatic FGF21 expression in vitro and in vivo and explored whether cAMP-responsive element-binding protein H (CREBH) was involved in the action of MS-275. Our results showed that MS-275 stimulated hepatic FGF21 mRNA and protein expressions in a dose- and time-dependent manner, as well as FGF21 secretion in primary mouse hepatocytes. Serum concentration and hepatic expression of FGF21 were elevated after injection of MS-275, along with increased expressions of genes involved in fatty acid oxidation and ketogenic production (peroxisome proliferator-activated receptor gammacoactivator1α, PGC-1α; carnitine palmitoyl-transferase 1a, CPT1a; 3-hydroxy-3-methylglutaryl-CoA synthase 2, Hmgcs2) as well as improved blood lipid profile. As a proved transcription factor of FGF21, the expression of CREBH was initiated by MS-275, with increased histone H3 lysine 18 acetylation (H3K18ac) signals and hepatocyte nuclear factor 4 alpha (HNF-4α) recruitment in CREBH promoter. Adenovirus-mediated knockdown of CREBH abolished MS-275-induced hepatic FGF21 and lipid metabolism-related gene expressions. These results suggest that MS-275 induces hepatic FGF21 by H3K18ac-mediated CREBH expression.